2021
DOI: 10.1039/d1gc02732h
|View full text |Cite
|
Sign up to set email alerts
|

Limonene dioxide as a building block for 100% bio-based thermosets

Abstract: This study valorises the benign epoxidation of (R)-(+)-limonene to generate novel bio-resourced limonene dioxide monomers. Without additional steps of separation or functionalization, the racemic limonene dioxide was cured with glutaric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
0
25
1
Order By: Relevance
“… 2 , 3 , 5 , 6 , 16 19 One well-known, low-cost sustainable raw material is limonene, which is extracted from citrus fruit peels and can be used as a monomer in the production of several polymers and blends. 20 , 21 One promising example is the work developed by Mija et al, 22 who used limonene dioxide and glutaric anhydride to obtain fully biobased thermoset materials. Moreover, polycarbonates and crosslinked polymers are other alternatives with potential applications in the coating and adhesive industry.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 5 , 6 , 16 19 One well-known, low-cost sustainable raw material is limonene, which is extracted from citrus fruit peels and can be used as a monomer in the production of several polymers and blends. 20 , 21 One promising example is the work developed by Mija et al, 22 who used limonene dioxide and glutaric anhydride to obtain fully biobased thermoset materials. Moreover, polycarbonates and crosslinked polymers are other alternatives with potential applications in the coating and adhesive industry.…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly evidenced when comparing our thermoset with similar biobased thermosets made from limonene-derived small organic molecules. For instance, Mija et al [5] were able to obtain a high elastic modulus (726 � 81 MPa) and tensile strength (34 � 3.5 MPa) for a fully biobased thermoset, which was prepared from limonene dioxide (LDO) and glutaric acid (GA). However, the elongation at break (5.44 � 0.69 %) was much lower than that found for the 1 : 1 PCO:Jeff thermoset (20.8 � 9.7 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] However, for the moment the development of more sustainable epoxy thermosets has received comparatively little attention. Mija et al [5] were the first to report a fully biobased thermoset composed of limonene dioxide and several biosourced anhydrides. Although there has been some recent development on the use of renewable epoxy derivatives, [6][7][8] most of the examples focused on the utilization of vegetable oils such as linseed oil, soybean, and castor oil among other, [9][10][11] and carbohydrates including isosorbide and itaconic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained material presents T g of 90 °C, a high degradation temperature (270 °C) and good mechanical properties: σ = 27 MPa; ɛ = 3,5 %; E = 1150 MPa; E' = 1650 MPa, SD = 78. [50] Following these results, we recently investigated the influence of cis-and trans-LDO stereochemistry on copolymerization with GA. For the first time we found that the cis-LDO generates thermosets with high mechanical properties (tan δ = 116 °C, σ = 43 MPa; ɛ = 4.56 %; E = 1.36 GPa; E' = 1.68 GPa, Shore D hardness = 81). [51]…”
Section: Copolymerization Of Limonene Dioxidementioning
confidence: 98%